The Effect of Early Life Antibiotic Exposures on Diarrheal Rates Among Young Children in Vellore, India. Issue 6 (June 2015) - Rogawski, Elizabeth T.; Westreich, Daniel; Becker-Dreps, Sylvia; Adair, Linda S.; Sandler, Robert S.; Sarkar, Rajiv; Kattula, Deepthi; Ward, Honorine D.; Meshnick, Steven R.; Kang, Gagandeep
Abstract : Background: Antibiotic treatment of childhood illnesses is common in India. In addition to contributing to antimicrobial resistance, antibiotics might result in increased susceptibility to diarrhea through interactions with the gastrointestinal microbiota. Breast milk, which enriches the microbiota early in life, may increase the resilience of the microbiota against perturbations by antibiotics. Methods: In a prospective observational cohort study, we assessed whether antibiotic exposures from birth to 6 months affected rates of diarrhea up to age 3 years among 465 children from Vellore, India. Adjusting for treatment indicators, we modeled diarrheal rates among children exposed and unexposed to antibiotics using negative binomial regression. We further assessed whether the effect of antibiotics on diarrheal rates was modified by exclusive breastfeeding at 6 months. Results: More than half of the children (n = 267, 57.4%) were given at least one course of antibiotics in the first 6 months of life. The adjusted relative incidence rate of diarrhea was 33% higher among children who received antibiotics under 6 months of age compared with those who did not (incidence rate ratio: 1.33, 95% confidence interval: 1.12, 1.57). Children who were exclusively breastfed until 6 months of age did not have increased diarrheal rates following antibiotic use. Conclusions: Antibiotic exposures early in life were associated with increased rates of diarrhea in early childhood. Exclusive breastfeeding might protect against this negative impact.